Effect of endotracheal tube plus stylet versus endotracheal tube alone on successful first-attempt tracheal intubation among critically ill patients: the multicentre randomised STYLETO study protocol. Issue 10 (7th October 2020) - Jaber, Samir; Rolle, Amélie; Jung, Boris; Chanques, Gerald; Bertet, Helena; Galeazzi, David; Chauveton, Claire; Molinari, Nicolas; De Jong, Audrey
Abstract : Introduction: Tracheal intubation is one of the most daily practiced procedures performed in intensive care unit (ICU). It is associated with severe life-threatening complications, which can lead to intubation-related cardiac arrest. Using a preshaped endotracheal tube plus stylet may have potential advantages over endotracheal tube without stylet. The stylet is a rigid but malleable introducer which fits inside the endotracheal tube and allows for manipulation of the tube shape; to facilitate passage of the tube through the laryngeal inlet. However, some complications from stylets have been reported including mucosal bleeding, perforation of the trachea or oesophagus and sore throat. The use of a stylet for first-attempt intubation has never been assessed in ICU and benefit remains to be established. Methods and analysis: The endotracheal tube plus stylet to increase first-attempt success during orotracheal intubation compared with endotracheal tube alone in ICU patients (STYLETO) trial is an investigator-initiated, multicentre, stratified, parallel-group unblinded trial with an electronic system-based randomisation. Patients will be randomly assigned to undergo the initial intubation attempt with endotracheal tube alone (ie, without stylet, control group) or endotracheal tube + stylet (experimental group). The primary outcome is the proportion of patients with successful first-attempt orotracheal intubation. The single, prespecified, secondary outcome is the incidence of complications related to intubation, in the hour following intubation. Other outcomes analysed will include safety, exploratory procedural and clinical outcomes. Ethics and dissemination: The study project has been approved by the appropriate ethics committee 'Comité-de-Protection-des-Personnes Nord-Ouest3-19.04.26.65808 Cat2 RECHMPL19_0216/STYLETO2019-A01180-57'". Informed consent is required. The results will be submitted for publication in a peer-reviewed journal and presented at one or more scientific conferences. If combined use of endotracheal tube plus stylet facilitates tracheal intubation of ICU patients compared with endotracheal tube alone, its use will become standard practice, thereby decreasing first-attempt intubation failure rates and, potentially, the frequency of intubation-related complications. Trial registration details: ClinicalTrials.gov Identifier: NCT04079387; Pre-results .